Writing for animation, comics, and games. - Marx, Christy, ....- (Amsterdam : Elsevier, 2007)
Writing for Animation, Comics, and Games explains the practical aspects of creating scripts for animation, comics, graphic novels, and computer games. It details how you can create scripts that are in the right industry format, and follow the expected rules for you to put your best foot forward to help you break-in to the trade. This book explains approaches to writing for exterior storytelling (animation, games); interior/exterior storytelling (comics and graphic novels), as well as considerations for non-linear computer games in the shortest, pithiest, and most economical way. The author offers insider's advice on how you can present work as professional, how to meet deadlines, how visual writing differs from prose, and the art of collaboration.